2022
DOI: 10.1167/iovs.63.5.12
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Proteomics for the Identification and Profiling of the Tear Proteome of Keratoconus Patients

Abstract: Purpose The qualitative approach followed in this study aims to obtain an extensive view of the keratoconus (KC) tear proteome, which could highlight proteins previously undetected and enlarge our knowledge of the disease's pathophysiology. Methods Twenty-five patients diagnosed with KC and 25 control subjects were studied in a prospective, cross-sectional study. KC screening examinations, including clinical and tomographic examinations, were performed on all participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Historically, lactoferrin (LF), IgE and MMP-9 have been the most common translational biomarkers studied in tear film and their usefulness has been validated in dry eye disease [ 119 ], allergic conjunctivitis [ 120 ], keratoconus [ 121 ] and inflammatory conjunctivitis [ 122 , 123 ]. As for nAMD, the use of two-dimensional electrophoresis followed by the MALDI-TOF/TOF mass spectrometry approach in a recent study [ 67 ] has led to the identification of a set of dysregulated tear film proteins including several proteins related to inflammation and neovascularization, such as allograft inflammatory factor 1 (AIF1), ATP-dependent translocase (ABCB1) and annexin-1.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, lactoferrin (LF), IgE and MMP-9 have been the most common translational biomarkers studied in tear film and their usefulness has been validated in dry eye disease [ 119 ], allergic conjunctivitis [ 120 ], keratoconus [ 121 ] and inflammatory conjunctivitis [ 122 , 123 ]. As for nAMD, the use of two-dimensional electrophoresis followed by the MALDI-TOF/TOF mass spectrometry approach in a recent study [ 67 ] has led to the identification of a set of dysregulated tear film proteins including several proteins related to inflammation and neovascularization, such as allograft inflammatory factor 1 (AIF1), ATP-dependent translocase (ABCB1) and annexin-1.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous research studies have recognized the role of oxidative stress, innate immunity, and inflammation pathways in the KC pathogenesis [ 125 , 126 ]. Higher levels of damaging free radicals and lower levels of antioxidant molecules were reported in KC samples [ 127 ].…”
Section: Ocular Surface Conditions With Lactoferrin-related Affectationmentioning
confidence: 99%
“…Self-created figure using elements with Creative Common (CC) license. The superscript numbers belong to the references cited in this manuscript [ 9 , 23 , 30 , 72 , 89 , 91 , 94 , 102 , 103 , 104 , 105 , 108 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 120 , 121 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ].…”
Section: Figurementioning
confidence: 99%
“…Alzheimer's dementia, Parkinson's disease, multiple sclerosis, breast cancer) 126 , 146 . Tear proteome profiling in keratoconus patients identified 58 proteins related to process of cell death, oxidative damage and inflammation specific to tears of patients with keratoconus; 41 proteins involved in iron pathways was found to be underexpressed in keratoconus patients and identified in control samples only 147 . Besides improving the knowledge of the disease's pathophysiology, Goni et al also analysed the tear proteome profile before and after treatments and identified biomarkers, mainly A-kinase anchor protein 13 (AKAP-13), altered by surgical treatment 148 .…”
Section: Novel Biomarkers For Diagnosis Treatment Effectiveness and P...mentioning
confidence: 99%